Deskripsi Kemampuan Koneksi Matematis Siswa Pada Materi Teorema Pythagoras - Arya Aurellio Yusuf; Nursiya Bito; Nurwan Nurwan; Perry Zakaria (Jambura Journal of Mathematics Education, 2022)
This article discusses the description of students' mathematical connection abilities in solving mathematics on the Pythagorean theorem material. This descriptive research was conducted at SMP Negeri 1 Bolaang Uki in the odd semester of the 2019/2020 school year. The technique of data collection is done by test. Description test to obtain mathematical connection ability data. The results showed that the students' mathematical connection ability to recognize and use connections between mathematical ideas was 45.14%, the indicator of understanding how mathematical ideas were connected and built on one another to produce a coherent whole was 29.63%, and indicators of the introduction and application of mathematics in daily life by 23.61%.